The Role of Host Species in Experimental Ferlavirus Infection: Comparison of a Single Strain in Ball Pythons (Python regius) and Corn Snakes (Pantherophis guttatus) - Michael Pees; Annkatrin Möller; Volker Schmidt; Wieland Schroedl; Rachel E. Marschang (Animals, 2023)
Ferlaviruses are a cause of respiratory disease in snakes. Four genogroups (A, B, C, and tortoise) have been described. Disease development is believed to depend on virus, host, and environment-specific factors. There is evidence of transmission of individual strains between genera and families of reptiles. A genogroup B virus previously used in a transmission study with corn snakes (Pantherophis guttatus) was applied intratracheally in ball pythons (Python regius) using the same protocol as for the corn snakes. Ball pythons became infected, with initial mild clinical signs noted four days post infection (p.i.), and the virus was detected first in the lungs on day 4 and spread to the intestine, pancreas, kidney and brain. Hematology showed an increase in circulating lymphocytes which peaked on day 28 p.i. Antibodies were detected beginning on day 16 and increased steadily to the end of the study. In comparison to corn snakes, ball pythons exhibited milder clinical signs and pathological changes, faster development of and higher antibody titers, and a hematological reaction dominated by lymphocytosis in contrast to heterophilia in corn snakes. These differences in host reaction to infection are important to understand ferlavirus epidemiology as well as for clinical medicine and diagnostic testing.